Recent changes in breast cancer incidence and mortality in Estonia: Transition to the west. (2nd June 2016) - Baburin, Aleksei; Aareleid, Tiiu; Rahu, Mati; Reedik, Lauri; Innos, Kaire
Abstract: Background The aim of this study was to examine breast cancer (BC) incidence and mortality trends in Estonia during recent decades and to compare the pattern of these trends with other selected European countries and regions. We attempt to explain the findings in relation to changes in Estonian society and healthcare system. Methods BC incidence (1985–2012) and mortality (1985–2013) data for Estonia were obtained from the Estonian Cancer Registry and Statistics Estonia. Data for selected European countries were obtained from the EUREG database. Joinpoint regression was used to analyze age-standardized rates in Estonia by age. For international comparison of incidence and mortality rates, we used scatterplot with 95% confidence ellipses and the mortality to incidence ratio. Results The overall BC incidence continues to increase in Estonia, while mortality has been in decline since 2000. Both incidence and mortality trends varied considerably across age groups. Among women aged 60 years and older, BC incidence increased at a rate of nearly 3% per year. Significant decrease in mortality was seen only among women aged 50–59 years. Comparison of scatterplots between countries and regions revealed two clusters in Europe separated along the incidence axis. The correlation between incidence and mortality in Estonia changed its direction in the mid-1990s. Conclusion In recent years, the dynamics of BC burden in Estonia has transitioned towards the high incidence–low mortality type model, which is characteristic to Western, Northern and Southern Europe. Although overall BC incidence is much lower in Estonia than in more affluent European countries, mortality from BC is still relatively high, particularly among elderly women.